(untitled) (REMUNOM, 2026)
Climate change has imposed increasing challenges on forestry, particularly in seasonal tropical regions, where rising temperatures, irregular precipitation patterns, and the intensification of extreme climatic events compromise the growth, survival, and productivity of forest plantations. In this context, the genus Eucalyptus plays a strategic role in Brazilian forestry due to its high productive potential, broad ecological plasticity, and importance for the pulp, biomass, and solid wood production chains. However, in environments such as the Brazilian Cerrado, maintaining productivity increasingly depends on the capacity of genetic materials to respond to water stress and climatic variability. Therefore, this study aimed to analyze, through a systematic literature review, the genetic adaptation of Eucalyptus to climatic stress and its implications for productivity in the Brazilian Cerrado. Methodologically, the research was characterized as a systematic review with a qualitative approach and exploratory nature, conducted following the guidelines of the PRISMA protocol. The literature search was performed in the Scopus and Web of Science databases using descriptors related to genetic improvement, drought tolerance, genotype × environment interaction, productivity, and climate change. Initially, 371 records were retrieved; after screening and eligibility stages, 30 articles composed the final corpus of the qualitative review. The interpretation of the selected studies was carried out using Bardin’s Content Analysis, allowing the organization of evidence into central analytical categories. The results indicated that the genetic adaptation of Eucalyptus is a decisive factor for maintaining forest productivity in environments subject to water deficit, as more adapted clones exhibit greater water-use efficiency, higher physiological stability, and better performance under limiting conditions. Furthermore, genotype × environment interaction, combined with the use of modern genetic selection tools, increases the accuracy of clonal recommendation and reduces productive and economic risks. It is concluded that genetic adaptation represents a strategic approach to increasing resilience, productive stability, and the sustainability of Eucalyptus forestry in the Cerrado under climate change scenarios.